Study of the behavior of tomato pulp microcapsules (Lycopersicum esculentum var. Carmen) immersed in extra virgin olive oil: product interaction and stability (Research, Society and Development, 2021)
The objective of this work was to microencapsulate the tomato pulp by the ionic gelation technique with 2% (M2) and 5% (M5) sodium alginate, immerse in extra virgin olive oil, characterize and evaluate the stability of this product during 60 days of storage. The analysis of lycopene content, carotenoids, antioxidant activity (ABTS), total phenolics, peroxide index, oxidative stability (Rancimat) and thermal (DSC) were performed in triplícate. The Tukey test was applied at the 5% level of significance. The formulations analyzed remained stable during storage, there was no significant difference in the levels of lycopene and carotenoids. The formulation M2 obtained minor interaction between the microencapsulated and olive oil (A2) about the phenolic content and antioxidant activity, in this way kept phenolic compounds trapped. The insertion of microcapsules in extra virgin olive oil has not quality decreased. The range required by the legislation regarding peroxide index was maintained and the oxidation induction time was not influenced. The DSC thermal analysis for the formulations M2 and M5 obtained peaks of dehydration (100 – 109°C) and degradation (390 – 400°C) in the same range,  showing thermal characteristics similar. The microcapsule/oil complex maintained the quality of the oil and added nutritional value. The type of encapsulated, or encapsulant, can be modified and a microcapsule can be obtained with different release characteristics.